Narrative as Moral Act: Guilt, Representation, and Incomplete Atonement in Joe Wright's Atonement (2007) - Marchella Putri Armelinda; Much. Koiri (Universitas Nurul Jadid, 2026)
Cinema functions as a significant cultural site for the negotiation of moral responsibility, yet the ethical dimensions of cinematic storytelling particularly how visual form actively constructs rather than merely illustrates moral meaning remain underexplored in existing scholarship on Atonement (2007). This study examines how Atonement (2007) represents writing as an ethical act through the character of Briony Tallis. The film explores the relationship between guilt, truth, and responsibility by showing how a single misunderstanding can create serious and lasting consequences. Using representation theory and narrative ethics, this study analyzes selected scenes, dialogue, and visual elements such as a framing, lighting, and character positioning. The analysis shows that Briony’s writing serves two functions: it becomes a way to express guilt, but it also allows her to control and reshape the story. Although her writing reflects regret and moral awareness, it cannot fully repair the harm she has caused. Therefore, the film presents atonement as an incomplete process that cannot be fully achieved through storytelling alone.